2018
DOI: 10.1016/j.jiac.2017.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Sustained improvement in vancomycin dosing and monitoring post-implementation of guidelines: Results of a three-year follow-up after a multifaceted intervention in an Australian teaching hospital

Abstract: A multifaceted intervention to implement a vancomycin dosing and monitoring guideline significantly improved prescribing, monitoring, pharmacokinetic and safety outcomes for patients treated with vancomycin over an extended period. However, increased guideline adoption by clinicians is required to maximize and prolong the utility of this important agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 43 publications
1
24
0
Order By: Relevance
“…Five of the six studies were from the US 35 , 36 , 38 40 and one from Australia. 37 Three studies reported the population as number of patients, with 263 in the intervention group and 274 receiving usual care, 35 37 and one study reported treatment courses, with 200 in the intervention group and 279 receiving usual care. 38 Two studies that evaluated timing of blood samples for vancomycin assays exclusively reported only the number of concentrations: 387 in the intervention group and 288 receiving usual care.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Five of the six studies were from the US 35 , 36 , 38 40 and one from Australia. 37 Three studies reported the population as number of patients, with 263 in the intervention group and 274 receiving usual care, 35 37 and one study reported treatment courses, with 200 in the intervention group and 279 receiving usual care. 38 Two studies that evaluated timing of blood samples for vancomycin assays exclusively reported only the number of concentrations: 387 in the intervention group and 288 receiving usual care.…”
Section: Resultsmentioning
confidence: 99%
“… 37 , 38 Two studies employed guidance and education meetings, 36 one utilized education meetings and dissemination of educational material, 40 and another used educational meetings only. 39 Of the four studies using guidance, two employed a clinical practice guideline, 37 , 38 one a nomogram, 36 and one an undefined policy change. 35 Dissemination of educational materials was employed in three studies using a pocket reference card ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our audit reflects current clinical practice for vancomycin in a large tertiary centre in Australia. Whilst internationally validated dosing guidelines for vancomycin are available, we have shown that best practice is not often followed, even in tertiary academic hospitals, despite the presence of multifaceted interventions such as dose calculators, hospital in‐service and availability of clinical pharmacists …”
Section: Discussionmentioning
confidence: 99%
“…Most studies of antimicrobial education for health professionals have been non‐specific, focusing on all antimicrobials, not vancomycin alone . While studies that report specifically on vancomycin education strategies report a reduction of inappropriate prescribing and improved TDM, it is important to note that these education strategies were delivered alongside other vancomycin‐specific interventions, including restricted prescribing or decision‐support systems . Thus, it is difficult to discern the contribution of the educational strategies alone to the improvements observed in vancomycin use.…”
Section: Introductionmentioning
confidence: 99%